Apple intake and cancer risk: a systematic review and meta-analysis of observational studies. Issue 14 (22nd March 2016) - Fabiani, Roberto; Minelli, Liliana; Rosignoli, Patrizia
Abstract: Objective: Conflicting results on the association between fruit consumption and cancer risk have been reported. Little is known about the cancer preventive effects of different fruit types. The present meta-analysis investigates whether an association exists between apple intake and cancer risk. Design: Relevant observational studies were identified by literature search (PubMed, Web of Science and Embase). A random-effect model was used to estimate the cancer risk in different anatomical sites. Between-study heterogeneity and publication bias were assessed using adequate statistical tests. Results: Twenty case–control (three on lung, five on colorectal, five on breast, two on oesophageal, three on oral cavity, two on prostate and one each on pancreas, bladder, larynx, ovary, kidney and brain cancer) and twenty-one cohort (seven on lung, two on colorectal, three on breast and one each on oesophageal, pancreas, bladder, kidney, endometrial, head–neck, urothelial and stomach cancer) studies met the inclusion criteria. Comparing the highest v. lowest level of apple consumption, the reduction of lung cancer risk was statistically highly significant in both case–control (OR=0·75; 95% CI 0·63, 0·88; P =0·001, I 2 =0 %) and cohort studies (relative risk=0·89; 95% CI 0·84, 0·94; P <0·001, I 2 =53 %). Instead, in the case of colorectal (OR=0·66; 95% CI 0·54, 0·81; P <0·001, I 2 =55%), breast (OR=0·79; 95% CI 0·73, 0·87; P <0·001, I 2 =1 %) and overall digestive tract (OR=0·50; 95% CI 0·36, 0·69; P <0·001, I 2 =90 %) cancers a significant preventive effect of apples was found only in case–control studies while prospective studies indicated no effect. No evidence of publication bias could be detected for colorectal, oral cavity, oesophageal and breast cancer. However, some confounding effects may be present and related to the consumption of other fruit which have not been considered as adjusting factors. Conclusions: The present meta-analysis indicates that consumption of apples is associated with a reduced risk of cancer in different anatomical sites.